The Relationship Between Breast Milk Coverage, Mother's Education Level, Sanitation Hygiene, and Infectional Diseases and Incidents Of Stunting In Toddler In Bangkalan District, East Java - Septa Katmawanti; Achmad Masfi; Ronal Surya Aditya; Dea Aflah Samah; Fatiya Rizka Putri; Oktavia Sri Wahyuni; Muhammad Fahmi Rabbani; Purnama Devita Sari (Preventia : The Indonesian Journal of Public Health, 2024)
Stunting remains a pressing global health issue, with 149 million children affected in 2020. In Bangkalan District, East Java, stunting prevalence reaches 25.2 percent, exceeding the provincial average of 19.2 percent. This study aimed to analyze factors influencing stunting, including breastfeeding coverage, maternal education, hygiene, and infectious diseases. Conducted from August to September 2023 in the Blega Health Center area, this analytical correlation study involved 35 toddlers aged 24–59 months selected through simple random sampling. Data were collected via questionnaires, anthropometric measurements, and interviews, then analyzed using chi-square tests in SPSS. The results revealed significant relationships between exclusive breastfeeding and stunting (p value is less than 0.05) and between infectious diseases (e.g., diarrhea and URTI) and stunting (p value is less than 0.05). Toddlers not exclusively breastfed were 0.2 times more likely to be stunted, and those frequently suffering from diarrhea had a 0.13 times higher risk. However, no significant association was found between maternal education or hygiene behavior and stunting (p value is more than 0.05). These findings emphasize the importance of promoting exclusive breastfeeding and preventing infectious diseases as key strategies to combat stunting. Complementary measures, such as improving hygiene and sanitation, remain critical to creating a supportive environment for child growth and development